Improving schools to promote learning - Walberg, Herbert J. (Emerald Publishing Limited : Information Age Publishing, 2010)
Improving Schools to Promote Learning is a concise and common-sense examination of all the moving parts that drive student learning. The book ties together the research, policies, and practices relative to the state, district, school, classroom, and family, and explains their effects on student learning. The author covers an array of topics, including technology, charter schools, turnaround initiatives, and instruction in specific subject areas.Herbert J. Walberg's book continues the work of previous publications from the Center on Innovation & Improvement (Handbook on Restructuring and Substantial School Improvement and Handbook on the Statewide Systems of Support) that connect research to practice at various levels of the education system. The book is accessible to a wide audience, including educators, school board members, parents, and policy makers. Walberg includes action steps in every chapter, providing practical recommendations for improved student achievement. The author also offers select references for additional material on the best research and most effective practices.